Solitudine e moltitudine, natura e città: Odilon Redon su Gustave Courbet (Materiali di Estetica. Terza serie, 2024)
The theme of solitude occupies a pivotal position in the artistic production and theoretical reflections of Gustave Courbet and Odilon Redon, two figures separated by distinct historical and stylistic frameworks but interconnected through their engagement with the existential dilemmas of modernity. This article undertakes a comparative analysis of their works and writings to investigate how solitude operates as a locus of artistic autonomy and a critical stance against the alienating forces of capitalist urbanization and industrial society in the 19th century. By intertwining materiality and imagination, both artists cultivate an ethical approach to isolation as a prerequisite for creative authenticity and freedom. Furthermore, this study explores the subterranean influence of Courbet’s materialism on Redon’s aesthetic strategies, shedding light on the interplay between realism and symbolism in their shared interrogation of the artist’s role within the cultural and social milieu of modernity.
Keywords: symbolism; solitude; realism; modernity; alienation